Fissure sealants: in vitro evaluation of abrasion wear and superficial roughness - Pardi,Vanessa (2008)
The aim of this study was to compare the in vitro wear and superficial roughness of four materials (Delton Dyract Flow, Dentsply; Filtek Flow, Vitremer, 3M ESPE) used as fissure sealant in 32 extracted human molars divided in four groups (n = 8) after abrasion with toothbrush/dentifrice. Impressions of each occlusal surface were made to analyze wear and circular specimens were prepared to analyze the roughness. Teeth and specimens were mounted in a toothbrushing machine. The replicas were observed using a SEM to determine the superficial wear. Wear: there were no statistically significant differences either between Delton and Filtek Flow or between Dyract Flow and Vitremer. Roughness: there were no statistical differences between Filtek Flow and Dyract Flow, Dyract Flow and Vitremer, Vitremer and Delton., Considering the clinical practice, if caries activity is present the use of Vitremer is suggested not only for its well known fluoride release, but it presented good roughness results.